Increasing Accountability through Budget Transparency at the Subnational Level in Cameroon - Alton, Martin Luis; Agarwal, Sanjay (World Bank, Washington, DC, 2014)
Improving governance is a major development challenge for Cameroon and for many other developing countries, and making public financial management more transparent is a central part of it. While budgets are public documents, accessible to citizens in principle, in practice, budget information is difficult to come by as a result of political, administrative, capacity, and logistical constraints as well as cost barriers at all tiers of government, including the national, regional, and municipal level and at service-delivery points like schools and health centers. In two of Cameroon s 10 regions, a World Bank-supported initiative has piloted a citizen-centered approach for disseminating simplified budget information of 151 schools, 58 health centers, and 28 municipalities and the two regional administrations. Budgets were made public and awareness was raised through various activities, including public community meetings at which the budgets of institutions were read aloud, poster campaigns, art competitions, theater performances, student budget clubs, and the use of media such as community radios and Facebook. Results of the initiative include increased tax revenues for one local council, changes in the willingness of parents to contribute to the financing of schools, and greater trust between mayors and constituents.